Editor’s Pick: Peritonitis in Peritoneal Dialysis Patients: The Case for Rapid Diagnosis, Targ - Aron Chakera (European Medical Journal Nephrology, 2018)
Peritoneal dialysis (PD) is a cost-effective, home-based treatment option for patients with end-stage renal disease; however, PD is declining in many countries. A major reason for this is peritonitis, which commonly leads to technique failure and has led to negative perceptions of PD by clinicians and patients. To restore confidence in PD, better diagnostics are required to enable appropriate treatment to be started earlier; this needs to be coupled with improved understanding of the biology of peritonitis. Advances in culture-independent microbiological methods, in particular the use of bacterial flow cytometry and immune fingerprinting techniques, can enable organism detection and antimicrobial susceptibility testing to be performed in as little as 3 hours after samples are received. At the same time, improved understanding of peritoneal mesothelial cell responses to infection is providing insights into pathways that may be targeted to dampen deleterious elementsof the host immune response, promote healing, and preserve membrane function.